The (in)completeness of local integrity systems, A cross-sectional study on municipal integrity systems for civil servants in the Netherlands - Montfort, André van; Ogric, Becir; Huberts, Leo (Archives of Business Research, 2018)
Private organizations and government bodies develop integrity systems that consist of various elements such as integrity officers, regulations, codes of conduct and supervision arrangements. For both the private and public sector there is little scientific knowledge about the extent to which local integrity systems are complete and factors that explain this (in)completeness. The present study focuses on local integrity systems for civil servants in the Netherlands. Using a theory-based evaluation framework it is concluded that Dutch municipal integrity systems differ substantially in terms of completeness. Contrary to our theoretical expectations, neither the number of inhabitants of a municipality nor the political composition of the municipal administration offers an explanation for this. The circumstance of whether or not a municipality is located in the most urbanized part of the Netherlands is, however, a relevant factor. The research findings open up challenging questions for future research on public and private integrity systems.